Transformations of phenolic compounds in cocoa shell during in vitro colonic fermentation - Silvia Cañas; Nicole Tosi; Vanesa Núñez-Gómez; Daniele Del Rio; Pedro Mena; Yolanda Aguilera; María A. Martín-Cabrejas (Current Research in Food Science)
Cocoa shell is a by-product generated by the cocoa processing industry, notable for its high content of phenolic compounds and methylxanthines, and recognized for their biological properties. The majority of cocoa phenolic compounds are not absorbed in the small intestine and reach the colon, where they can be catabolized by the gut microbiota, influencing their bioavailability and bioactivity. This research aimed to study the changes that phenolic compounds from cocoa shell flour (CSF) and extract (CSE) undergo during colonic fermentation after gastrointestinal digestion, using an in vitro model and a targeted metabolomics approach. A decrease in the concentration of most parental phenolic compounds was observed, with a simultaneous increase in phenyl-γ-valerolactones, phenylvaleric acids, and phenylpropanoic acids. Benzoic acids, phenylpropanoic acids, phenylacetic acids, and benzaldehydes were the compounds found in the highest concentrations. Additionally, phenolic compounds in CSF were metabolized more slowly than those in CSE. This may be due to the matrix effect that protects the compounds from degradation during colonic fermentation. These findings further support the potential of cocoa shells as a food ingredient rich in phenolic compounds and bioavailable metabolites, which may exert beneficial effects in the colon and at the systemic level.